Zinc oxide varistor and preparation method thereof
Through composite powder technology and ultrafine grinding dispersion combined with three-stage sintering, the preparation process of zinc oxide varistor plates is simplified, and the problems of insufficient resistance of existing resistor plates under multiple lightning conditions and complex preparation process are solved, thereby achieving efficient and low-cost resistor plate production.
Patent Information
- Application Number
- CN202411912782.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing zinc oxide varistor plates have insufficient tolerance under multiple lightning conditions, and the preparation process is complex and energy consumption is high, resulting in increased production costs and environmental pollution.
The zinc oxide varistor sheet is prepared by composite powder technology, and the composite powder is prepared by co-precipitation method to reduce the high-temperature calcination step, and combined with ultrafine grinding dispersion and three-stage sintering process to simplify the preparation process and reduce energy consumption.
It improves the flow capacity and electrical performance consistency of the resistor plate, reduces the production cost and energy consumption of the resistor plate, reduces environmental pollution, and reduces the amount of additives while ensuring performance.
Smart Images

Figure BDA0005206145180000141 
Figure FDA0005206145170000011 
Figure HDA0005206145190000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resistor sheet manufacturing, and in particular to a zinc oxide varistor sheet and a preparation method thereof. Background Art
[0002] Lightning strikes are one of the main causes of power system failures. As an important lightning protection device, lightning arresters are responsible for absorbing and releasing lightning impulse energy. Zinc oxide varistors are the core components of lightning arresters, and the electrical properties of the resistors determine the performance of the arresters. In recent years, with the continuous development of the power industry, the failure phenomena encountered by lightning arresters have been further counted and analyzed in depth. The phenomenon of lightning arresters encountering multiple lightning strikes has continued to increase in recent years and has attracted industry attention. The impact of multiple lightning strikes on lightning arresters and how to determine the multiple lightning withstand capacity of lightning arresters have gradually become the direction of industry research. The residual voltage of the resistor determines the protection level of the arrester. The lower the residual voltage, the higher the protection level. And the current carrying capacity of the resistor has gradually become an important factor restricting the development of lightning arresters. Therefore, research on resistors with low residual voltage and high current carrying capacity has gradually become the direction of industry research.
[0003] In order to solve the above problems, the existing solutions in the prior art are mainly to improve the current carrying capacity of the resistor by optimizing the resistor formula and improving the temperature characteristics of the resistor, or to improve the microscopic uniformity of the resistor and the current carrying capacity of the resistor by improving the manufacturing process and enhancing the uniformity of the raw material mixing. At present, some technicians have proposed to use composite powder to prepare zinc oxide varistors, enhance the dispersion of raw materials, and improve the microstructure of the resistor, such as patents CN116092761A and CN113149634A.
[0004] Although the existing technology has improved the current carrying capacity of resistors to a certain extent, there are still some problems and shortcomings in practical applications. Starting from the formulation, the performance of resistors can be directly improved, but this research has been carried out for a long time, there are many literatures, and it is difficult to seek innovative breakthroughs. The composite powder technology is less used in the field of resistor preparation and is a relatively new technology. The composite powder technology currently used in the field of resistor preparation is often prepared by co-precipitation or sol-gel method. The composite powder needs to be calcined at high temperature before it can be used in the preparation of zinc oxide resistors, which will increase a lot of energy consumption and is inconsistent with the energy conservation and emission reduction concept advocated by the current society. Secondly, the existing preparation method is complicated and has many steps, which increases the production cost. Therefore, how to simplify the preparation process, reduce energy consumption, and reduce environmental pollution while ensuring the performance of the resistor is an urgent problem to be solved in the current resistor manufacturing field. Summary of the invention
[0005] In view of this, the present invention provides a zinc oxide varistor sheet and a preparation method thereof. The preparation method of the present invention can reduce the voltage ratio of the resistor sheet, improve the square wave 2ms capacity bearing capacity, and optimize the consistency of electrical performance.
[0006] The present invention provides a method for preparing a zinc oxide varistor sheet, comprising the following steps:
[0007] A) mixing Bi salt, Sb salt, Mn salt, Ni salt, Co salt and water to obtain a metal salt mixed solution;
[0008] B) adding a precipitant and a precipitation aid to the metal salt solution in sequence to obtain a solution to be precipitated;
[0009] C) allowing the solution to be precipitated to settle and separate the solid from the liquid to obtain a precipitate; then, washing and drying the precipitate to obtain a composite powder;
[0010] D) subjecting the composite powder, water, ZnO powder and binder to ultrafine grinding and dispersion treatment to obtain a slurry;
[0011] E) spray drying the slurry to obtain granules; then, pressing and molding to obtain a green body;
[0012] F) heat-insulating the green body in an open atmosphere to remove binder, then pre-sintering it in a closed atmosphere, and then sintering it in a closed atmosphere to obtain a sintered green body; then, performing surface treatment to obtain a resistor;
[0013] in,
[0014] The temperature of the heat preservation debinding is 350-500°C and the time is 2-3h;
[0015] The pre-sintering temperature is 750-950°C and the time is 2-3h;
[0016] The sintering temperature is 1050-1150° C. and the sintering time is 2-3 hours.
[0017] Preferably, in step A):
[0018] The Bi salt is at least one of bismuth nitrate, bismuth chloride and bismuth citrate;
[0019] The Sb salt is at least one of antimony nitrate, antimony chloride and antimony citrate;
[0020] The Mn salt is at least one of manganese nitrate, manganese chloride and manganese citrate;
[0021] The Ni salt is at least one of nickel nitrate, nickel chloride and nickel citrate;
[0022] The Co salt is at least one of cobalt nitrate, cobalt chloride and cobalt citrate.
[0023] Preferably, in step A), the amount of each metal salt is as follows, measured in molar percentage of the metal element:
[0024] Bi 20-30 mol%;
[0025] Sb 20-30 mol%;
[0026] Mn 10-20 mol%;
[0027] Ni 10-20 mol%;
[0028] Co 10-20 mol%;
[0029] The concentration of the metal salt mixed solution is 0.5-1.0 mol / L.
[0030] Preferably, in step B), the precipitant and the precipitation aid are matched as follows:
[0031] The precipitant is Na2CO3, and the precipitation aid is NaHCO3;
[0032] or
[0033] The precipitant is NH4OH and the precipitation aid is NH4HCO3.
[0034] Preferably, in step B), the molar amount of the precipitant is 103% to 110% of the total molar amount of metal ions in the metal salt solution.
[0035] Preferably, in step C), the temperature of the static precipitation is preferably 40-50° C., and the time is 1-2 h.
[0036] Preferably, step D) specifically comprises: mixing the composite powder with water and performing ultrafine grinding and dispersion to obtain composite powder slurry; and then adding ZnO powder, a binder and water and continuing ultrafine grinding and dispersion to obtain slurry.
[0037] Preferably, when the composite powder is mixed with water for ultrafine grinding and dispersion, the mass ratio of water to composite powder is (1.5-2):1; the speed of the ultrafine grinding and dispersion is 3000-5000 rpm, and the time is 1-2 hours;
[0038] When adding ZnO powder, binder and water to continue ultrafine grinding and dispersion, the amount of ZnO powder is 85% to 90% of the total mass of the composite powder and ZnO powder; the mass ratio of water to the composite powder slurry obtained in the previous step is (0.5 to 1): 1; the rotation speed of the continued ultrafine grinding and dispersion is 3000 to 5000 rpm, and the time is 1 to 2 hours.
[0039] Preferably, in step E), the moisture content of the granular material is 1.2±0.1%; the pressure of the compression molding is 5-10 MPa, and the holding time is 8-10 s.
[0040] The present invention also provides a zinc oxide varistor sheet prepared by the preparation method described in the above technical solution.
[0041] The preparation method provided by the present invention uses composite powder technology to configure various additives into a metal salt solution, and after adding a precipitant and a precipitation aid, a co-precipitation occurs to obtain a uniform additive precipitate, which is mixed with zinc oxide after centrifugal cleaning, and then ultrafinely ground and dispersed to ensure the redispersion of the additive and the uniform distribution of the additive in the zinc oxide, and finally obtain a slurry with uniform particle size and good dispersibility. This slurry is used for granulation, water-containing, molding, sintering, painting, grinding, and aluminum spraying to prepare a resistor. The above method of the present invention can make the additives evenly dispersed in the resistor, ensure the consistency of the resistor microstructure, and the prepared resistor has the advantages of low pressure ratio, high square wave 2ms capacity tolerance, and good consistency of electrical measurement performance. It can also reduce the amount of additives added and reduce the production cost of the resistor. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0043] Figure 1 Schematic diagram of the preparation method of the embodiment of the present invention;
[0044] Figure 2 It is the SEM image of the samples of Examples 1-2 and Comparative Example 1. DETAILED DESCRIPTION
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0046] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0047] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0048] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0049] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 350-500℃ means that the units of the left endpoint "350" and the right endpoint "500" are both ℃.
[0050] The present invention provides a method for preparing a zinc oxide varistor, comprising the following steps:
[0051] A) mixing Bi salt, Sb salt, Mn salt, Ni salt, Co salt and water to obtain a metal salt mixed solution;
[0052] B) adding a precipitant and a precipitation aid to the metal salt solution in sequence to obtain a solution to be precipitated;
[0053] C) allowing the solution to be precipitated to settle and separate the solid from the liquid to obtain a precipitate; then, washing and drying the precipitate to obtain a composite powder;
[0054] D) subjecting the composite powder, water, ZnO powder and binder to ultrafine grinding and dispersion treatment to obtain a slurry;
[0055] E) spray drying the slurry to obtain granules; then, pressing and molding to obtain a green body;
[0056] F) heat-insulating the green body in an open atmosphere to remove binder, then pre-sintering it in a closed atmosphere, and then sintering it in a closed atmosphere to obtain a sintered green body; then, performing surface treatment to obtain a resistor;
[0057] in,
[0058] The temperature of the heat preservation debinding is 350-500°C and the time is 2-3h;
[0059] The pre-sintering temperature is 750-950°C and the time is 2-3h;
[0060] The sintering temperature is 1050-1150° C. and the sintering time is 2-3 hours.
[0061] Compared with the prior art, the present invention solves the following problems: (1) improving the current carrying capacity of the resistor and optimizing the performance consistency of the resistor; (2) simplifying the preparation process, reducing the amount of additives added, and reducing energy consumption and production costs.
[0062] [About Step A]:
[0063] A) Bi salt, Sb salt, Mn salt, Ni salt, Co salt and water are mixed to obtain a metal salt mixed solution.
[0064] In the present invention, the Bi salt (i.e., bismuth metal salt) is preferably at least one of bismuth nitrate, bismuth chloride and bismuth citrate. In the present invention, the Sb salt (i.e., antimony metal salt) is preferably at least one of antimony nitrate, antimony chloride and antimony citrate. In the present invention, the Mn salt (i.e., manganese metal salt) is preferably at least one of manganese nitrate, manganese chloride and manganese citrate. In the present invention, the Ni salt (i.e., nickel metal salt) is preferably at least one of nickel nitrate, nickel chloride and nickel citrate. In the present invention, the Co salt (i.e., cobalt metal salt) is preferably at least one of cobalt nitrate, cobalt chloride and cobalt citrate.
[0065] In the present invention, the amounts of the five metal salts are as follows, based on the molar percentage of the metal elements:
[0066] Bi 20-30 mol%;
[0067] Sb 20-30 mol%;
[0068] Mn 10-20 mol%;
[0069] Ni 10-20 mol%;
[0070] Co 10~20mol%.
[0071] The molar percentage of Bi may be 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%. The molar percentage of Sb may be 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%. The molar percentage of Mn may be 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%. The molar percentage of Ni can be specifically 10mol%, 11mol%, 12mol%, 13mol%, 14mol%, 15mol%, 16mol%, 17mol%, 18mol%, 19mol%, 20mol%. The molar percentage of Co can be specifically 10mol%, 11mol%, 12mol%, 13mol%, 14mol%, 15mol%, 16mol%, 17mol%, 18mol%, 19mol%, 20mol%. The total molar amount of the above five metal elements is preferably 100mol%.
[0072] In the present invention, the water is preferably deionized water.
[0073] In the present invention, when Bi salt, Sb salt, Mn salt, Ni salt, Co salt and water are mixed, the amount of metal salt and water used is preferably such that the concentration of the obtained metal salt mixture is 0.5 to 1.0 mol / L, specifically 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L.
[0074] [About step B]:
[0075] B) adding a precipitant and a precipitation aid to the metal salt solution in sequence to obtain a solution to be precipitated.
[0076] In the present invention, the precipitant and the precipitation aid are used in pairs, preferably as follows: the precipitant is Na2CO3 and the precipitation aid is NaHCO3; or, the precipitant is NH4OH and the precipitation aid is NH4HCO3.
[0077] In the present invention, the molar amount of the precipitant is preferably higher than 3% of the total molar amount of metal ions in the metal salt solution, more preferably 103% to 110% of the total molar amount of metal ions in the metal salt solution, specifically 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%.
[0078] In the present invention, the precipitation aid is preferably added in the form of a solution, that is, a precipitation aid solution is added. The precipitation aid solution is an aqueous solution of the precipitation aid. The pH value of the precipitation aid adjustment system is preferably adjusted to 8 to 10, specifically 8, 9, 10; introducing the precipitation aid and controlling the pH under the above conditions is conducive to further improving the metal ion precipitation efficiency. After adding the precipitant and precipitation aid, stir thoroughly to obtain a solution to be precipitated.
[0079] [About Step C]:
[0080] C) allowing the solution to be precipitated to settle and separate the solid from the liquid to obtain a precipitate; then, washing and drying the precipitate to obtain a composite powder.
[0081] In the present invention, the temperature of the static precipitation is preferably 40-50°C, specifically 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, more preferably 40°C. The required temperature can be provided by a constant temperature water bath. In the present invention, the time of the static precipitation is preferably 1-2h, specifically 1h, 2h.
[0082] In the present invention, after static precipitation, solid-liquid separation is performed. In the present invention, the method of solid-liquid separation is not particularly limited and can be a conventional method in the art, such as filtration. After solid-liquid separation, a solid precipitate is obtained.
[0083] In the present invention, after obtaining the solid precipitate, washing and drying are performed. The washing is preferably centrifugal washing. The washing is preferably first washed with water and then washed with alcohol. After the above washing, drying is performed to obtain a composite powder.
[0084] [About Step D]:
[0085] D) subjecting the composite powder, water, ZnO powder and binder to ultrafine grinding and dispersion treatment to obtain slurry.
[0086] In the present invention, step D) preferably specifically comprises: mixing the composite powder with water and performing ultrafine grinding and dispersion to obtain composite powder slurry; and then adding ZnO powder, a binder and water and continuing ultrafine grinding and dispersion to obtain slurry.
[0087] in,
[0088] When the composite powder is mixed with water for ultrafine grinding and dispersion, the mass ratio of water to composite powder is preferably (1.5-2):1, specifically 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1. The ultrafine grinding dispersion is achieved by an ultrafine grinding dispersion device. The rotation speed of the ultrafine grinding dispersion is preferably 3000-5000rpm, specifically 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm. The ultrafine grinding dispersion time is preferably 1-2h, specifically 1h, 2h. After the above ultrafine grinding dispersion, a composite powder slurry is obtained.
[0089] When adding ZnO powder, binder and water to continue ultrafine grinding and dispersion, the amount of ZnO powder is preferably 85% to 90% of the total mass of the composite powder and ZnO powder, and can be specifically 85%, 86%, 87%, 88%, 89%, 90%. The type of the binder is not particularly limited, and can be a conventional binder in the field, including but not limited to at least one of polyvinyl alcohol and polyethylene glycol. The amount of the binder is preferably 5% to 10% of the mass of the ZnO powder, and can be specifically 5%, 6%, 7%, 8%, 9%, 10%. The mass ratio of water to the composite powder slurry obtained in the previous step is preferably (0.5 to 1): 1, and can be specifically 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1.0: 1. The rotation speed of the continuous ultrafine grinding and dispersing is preferably 3000-5000rpm, specifically 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm, and more preferably the same as the rotation speed of the previous ultrafine grinding and dispersing. The time of the continuous ultrafine grinding and dispersing is preferably 1-2h, specifically 1h, 2h. After the above ultrafine grinding and dispersing, a mixed slurry is obtained.
[0090] [About Step E]:
[0091] E) spray drying the slurry to obtain granules; and then pressing and molding to obtain a green body.
[0092] In the present invention, after the slurry is obtained in step D), it is spray-dried to obtain granules. In the present invention, when spray-drying, the moisture content of the obtained granules is preferably controlled to be 1.2±0.1%.
[0093] In the present invention, after the above-mentioned spray drying, it is preferably also aged. Then, a hydraulic press and a cylindrical mold are used for water-containing compression molding. Wherein, the diameter of the cylindrical mold is preferably 52mm. The pressure of the compression molding is preferably 5-10MPa, specifically 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, and more preferably 10MPa. The holding time of the compression molding is preferably 8-10s, specifically 8s, 9s, 10s. After the above-mentioned compression molding, a green body is obtained.
[0094] [About Step F]:
[0095] F) keeping the green body warm under open atmosphere to remove binder, then pre-sintering under closed atmosphere, and then sintering under closed atmosphere to obtain a sintered green body; then, performing surface treatment to obtain a resistor.
[0096] In the present invention, the open atmosphere condition refers to an open container, specifically an open sagger. The closed atmosphere condition refers to a closed container, specifically a closed sagger.
[0097] The present invention performs three-stage heat treatment:
[0098] The first heat treatment is heat preservation and debinding under open atmosphere conditions. The temperature of the heat preservation and debinding is 350-500°C, specifically 350°C, 400°C, 450°C, 500°C, and more preferably 400-500°C. The time of the heat preservation and debinding is 2-3h, specifically 2h, 2.5h, 3h.
[0099] The second stage of heat treatment is pre-sintering under closed atmosphere conditions. The pre-sintering temperature is 750-950°C, specifically 750°C, 800°C, 850°C, 900°C, 950°C, more preferably 850-950°C. The pre-sintering time is 2-3h, specifically 2h, 2.5h, 3h. The composite powder is decomposed and the green body is pre-sintered by the above pre-sintering.
[0100] The third stage of heat treatment is sintering under closed atmosphere conditions; specifically, the temperature is raised from room temperature to the sintering temperature under closed atmosphere conditions for heat preservation sintering. The sintering temperature is 1050-1150°C, specifically 1050°C, 1100°C, 1150°C. The sintering insulation time is 2-3h, specifically 2h, 2.5h, 3h. The third stage is used for sintering and densification to form a dense ceramic body. After the above three-stage heat treatment, a sintered body is obtained.
[0101] In the present invention, after the sintered green body is obtained, the surface treatment is performed. The present invention has no special restrictions on the surface treatment, which is a conventional treatment process for the green body when preparing resistors in the art; specifically, it includes spraying paint, grinding and aluminum spraying, so as to obtain the resistor.
[0102] The present invention also provides a zinc oxide varistor sheet prepared by the preparation method described in the above technical solution.
[0103] The main technical means and advantages adopted by the present invention are as follows: (1) The composite powder is prepared by co-precipitation method. After centrifugal cleaning, calcination is not required, and it is directly dispersed by ball milling with zinc oxide, which reduces the preparation process and reduces energy consumption; (2) Ultrafine grinding is used as the ball milling dispersion method to further improve the dispersibility of the raw materials. (3) A three-stage sintering method is adopted to complete the debinding, composite powder decomposition and resistor pre-sintering and sintering at one time, simplifying the sintering procedure, improving the density of the resistor, and optimizing the performance consistency of the resistor. (4) By optimizing the production process of the resistor, the entire resistor production cycle and energy consumption are significantly reduced. The present invention can reduce the use of additives while ensuring the performance of the resistor, which not only improves the production efficiency, but also reduces the production cost, and has a high economic value.
[0104] Compared with the prior art, the present invention has the following beneficial effects: 1. Reduced energy consumption: Since the present invention does not require high-temperature calcination of composite powder, energy consumption is reduced, which is in line with the concept of energy conservation and emission reduction advocated by the current society. 2. Excellent performance: The present invention improves the performance of the resistor from three perspectives. First, the composite powder technology is used to evenly disperse the additives. Second, ultrafine grinding is used to further improve the dispersibility of the raw materials. Third, a three-step sintering method is used to improve the density of the resistor and optimize the consistency of the resistor performance. 3. Reduced production costs: Since the preparation method of the present invention is simple, energy consumption is low, and the amount of additives used is small, it can effectively reduce production costs and has high economic value.
[0105] Due to the advanced nature of the technical solution of the present invention, it can be widely used in the fields of lightning arrester manufacturing, resistor manufacturing, and co-firing of ceramic insulating materials. First, the resistor of the present invention has high performance consistency, superior pressure ratio, and high current density, which can reduce the number of resistors used in lightning arresters and improve the performance of lightning arresters. Secondly, the preparation method of the present invention is simple, has low energy consumption, and uses a small amount of additives, which can greatly reduce the production cost of resistors and meet the market demand for high-efficiency and low-cost resistors. Therefore, the present invention has broad market application prospects and needs.
[0106] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0107] Example 1
[0108] 1. Sample preparation
[0109] according to Figure 1The preparation process shown is as follows:
[0110] A) According to the following ratios, Bi (25 mol%), Sb (30 mol%), Mn (10 mol%), Ni (20 mol%), and Co (15 mol%) were weighed and dissolved in water to a concentration of 0.5 mol / L. The mixture was stirred evenly to obtain a metal salt mixture.
[0111] B) adding a precipitant Na2CO3 to the metal salt solution in an amount of 105% of the total molar amount of metal ions, and then adding a precipitation aid NaHCO3 solution, adjusting the pH to 8, and stirring sufficiently to obtain a solution to be precipitated.
[0112] C) The solution to be precipitated is placed in a constant temperature water bath at 40°C for 1 hour for precipitation, and filtered to obtain a precipitate. Then, the precipitate is centrifuged and washed, first by centrifugation with pure water for 3 times, then by centrifugation with alcohol for 2 times, and then dried after washing to obtain a composite powder.
[0113] D) The composite powder and deionized water were mixed in a mass ratio of 1:2, and ultrafinely ground and dispersed at 3000 rpm for 1 hour to obtain a composite powder slurry. Then, ZnO powder (the amount was 90% of the total mass of the composite powder and ZnO powder), binder polyvinyl alcohol (the amount was 6% of the mass of ZnO powder) and deionized water (the mass ratio of deionized water to composite powder slurry was 1:1) were added, and ultrafinely ground and dispersed at the above speed for 1 hour to obtain a mixed slurry.
[0114] E) spray drying the obtained mixed slurry to obtain granules with a water content of 1.2±0.1%. After aging, the granules are pressed into a shape using a hydraulic pressure and a cylindrical mold with a diameter of 52 mm, with a molding pressure of 10 MPa and a pressure holding time of 8 seconds to obtain a green body.
[0115] F) The green body is kept at 400°C for 2 hours under open atmosphere to remove binder, and then pre-sintered at 900°C for 2 hours under closed atmosphere, and then heated from room temperature to 1080°C for 2 hours under closed conditions to obtain a sintered green body. Then, it is sprayed with paint, polished and aluminum-sprayed to obtain a zinc oxide resistor.
[0116] 2. Sample testing
[0117] (2.1) Electrical performance test:
[0118] The obtained resistor was subjected to various electrical performance tests, and each performance was tested 5 times. The results are shown in Table 1.
[0119] Table 1: Electrical parameters of the resistor in Example 1
[0120] serial number Gradient (V / mm) <![CDATA[Pressure ratio U 10kA / U 1mA > <![CDATA[Leakage current (μA / cm 2 )]]> 1 229 1.65 3 2 228 1.64 2 3 227 1.65 2 4 228 1.66 3 5 228 1.65 2 average value 228 1.65 2.4
[0121] (2.2) Square wave capacity test:
[0122] The 800A square wave 2ms capacity test and the 1000A square wave 2ms capacity test were performed respectively, and each test was repeated 5 times. The results are shown in Table 2.
[0123] Table 2: Square wave 2ms capacity test results of the resistor in Example 1
[0124] serial number 800A square wave capacity 1000A square wave capacity 1 Pass Pass 2 Pass Pass 3 Pass Pass 4 Pass Pass 5 Pass Pass Pass Rate 100% 100%
[0125] Example 2
[0126] 1. Sample preparation
[0127] A) According to the following ratios, Bi (25 mol%), Sb (25 mol%), Mn (15 mol%), Ni (20 mol%), and Co (15 mol%) were weighed and dissolved in water to a concentration of 0.5 mol / L. The mixture was stirred evenly to obtain a metal salt mixture.
[0128] B) Add NH4OH solution as a precipitant to the metal salt solution in an amount of 105% of the total molar amount of metal ions, then add NH4HCO3 solution as a precipitation aid, adjust the pH to 10, and stir thoroughly to obtain a solution to be precipitated.
[0129] C) The solution to be precipitated is placed in a constant temperature water bath at 40°C for 1 hour for precipitation, and filtered to obtain a precipitate. Then, the precipitate is centrifuged and washed, first by centrifugation with pure water for 3 times, then by centrifugation with alcohol for 2 times, and then dried after washing to obtain a composite powder.
[0130] D) The composite powder and deionized water were mixed in a mass ratio of 1:2, and ultrafinely ground and dispersed at 5000 rpm for 1 hour to obtain a composite powder slurry. Then, ZnO powder (the amount was 95% of the total mass of the composite powder and ZnO powder), binder polyvinyl alcohol (the amount was 5% of the mass of ZnO powder) and deionized water (the mass ratio of deionized water to composite powder slurry was 1:1) were added, and ultrafinely ground and dispersed at the above speed for 1 hour to obtain a mixed slurry.
[0131] E) The obtained mixed slurry is spray dried to obtain granules with a water content of 1.2±0.1%. After aging, the granules are pressed into a shape using a hydraulic and cylindrical mold with a diameter of 52 mm, with a molding pressure of 10 MPa and a pressure holding time of 10 seconds to obtain a green body.
[0132] F) The green body is kept at 450°C for 2 hours under open atmosphere to remove binder, and then pre-sintered at 950°C for 2 hours under closed atmosphere, and then sintered from room temperature to 1100°C for 2 hours under closed conditions to obtain a sintered green body. Then, the same surface treatment as in Example 1 is performed to obtain a zinc oxide resistor.
[0133] 2. Sample testing
[0134] (2.1) Electrical performance test:
[0135] The test was carried out according to the test method of Example 1, and the results are shown in Table 3.
[0136] Table 3: Electrical parameters of the resistor in Example 2
[0137] serial number Gradient (V / mm) <![CDATA[Pressure ratio U 10kA / U 1mA > <![CDATA[Leakage current (μA / cm 2 )]]> 1 217 1.66 2 2 216 1.67 1 3 216 1.66 1 4 217 1.66 2 5 216 1.66 1 average value 216 1.66 1
[0138] (2.2) Square wave capacity test:
[0139] The test was carried out according to the test method of Example 1, and the results are shown in Table 4.
[0140] Table 4: Square wave 2ms capacity test results of the resistor in Example 2
[0141] serial number 800A square wave capacity 1000A square wave capacity 1 Pass Pass 2 Pass Pass 3 Pass Pass 4 Pass Pass 5 Pass Pass Pass Rate 100% 100%
[0142] Comparative Example 1
[0143] 1. Sample preparation
[0144] The comparative sample was prepared by using a conventional resistor preparation method, and the metal oxide powders of the several components in the formula were ball-milled, granulated, and sintered to obtain the sample. The details are as follows:
[0145] S1. Weigh the corresponding oxide powders of Bi (25 mol%), Sb (30 mol%), Mn (10 mol%), Ni (20 mol%), and Co (15 mol%) and mix them according to the following proportions. Add appropriate amount of deionized water (the ratio of water to total mass of powder is 2:1), and disperse them by ultrafine grinding at 3000 rpm for 1 h to obtain a mixed powder slurry.
[0146] S2. Add ZnO powder (the amount is 90% of the total mass of the mixed powder and ZnO powder), binder polyvinyl alcohol (the amount is 6% of the mass of ZnO powder) and deionized water (the mass ratio of deionized water to mixed powder slurry is 1:1) to the mixed powder slurry, and continue ultrafine grinding and dispersion at the above speed for 1 hour to obtain a mixed slurry.
[0147] S3, the same as step E) of Example 1, spray drying the obtained mixed slurry to obtain granules with a water content of 1.2±0.1%. After aging, the granules are pressed into a shape using a hydraulic and 52mm diameter cylindrical mold, with a molding pressure of 10MPa and a pressure holding time of 8s to obtain a green body.
[0148] S4, same as step F) of Example 1, the green body is kept at 400°C for 2 hours in an open atmosphere to remove binder, then pre-sintered at 900°C for 2 hours in a closed atmosphere, and then heated from room temperature to 1080°C for 2 hours in a closed atmosphere to obtain a sintered green body. Then, it is sprayed with paint, polished and aluminum-sprayed to obtain a zinc oxide resistor.
[0149] 2. Sample testing
[0150] (2.1) Electrical performance test:
[0151] The test was carried out according to the test method of Example 1, and the results are shown in Table 5.
[0152] Table 5: Electrical parameters of resistors in comparative example 1
[0153] serial number Gradient (V / mm) <![CDATA[Pressure ratio U 10kA / U 1mA > <![CDATA[Leakage current (μA / cm 2 )]]> 1 224 1.68 4 2 223 1.69 2 3 227 1.67 2 4 225 1.70 1 5 224 1.69 3 average value 225 1.69 2.4
[0154] (2.2) Square wave capacity test:
[0155] The test was carried out according to the test method of Example 1, and the results are shown in Table 6.
[0156] Table 6: Square wave 2ms capacity test results of the resistor in comparative example 1
[0157] serial number 800A square wave capacity 1000A square wave capacity 1 Pass Pass 2 Pass Fail 3 Pass Pass 4 Pass Fail 5 Fail / Pass Rate 80% 50%
[0158] Performance comparison :
[0159] 1. Comparison of electrical properties
[0160] The performance comparison of Examples 1-2 and Comparative Example 1 is shown in Table 7.
[0161] Table 7: Performance comparison of samples of Examples 1-2 and Comparative Example 1
[0162]
[0163] The same additive ratio was selected for Example 1 and Comparative Example 1, and the additive addition amount was 10wt%, which is about the lower limit of the additive addition amount in the conventional preparation method of the resistor. The additive addition amount in Example 2 was only 5wt%, which is only half of the lower limit of the additive addition amount in the conventional preparation method of the resistor. It can be seen from the experimental results that the sample of the embodiment has a better pressure ratio than the comparative sample, a higher square wave 2ms capacity tolerance, and a higher tolerable energy density. Moreover, when only half of the additives are added, the performance of Example 2 is not significantly reduced compared with that of Example 1, and is still better than Comparative Example 1 of the conventional preparation method. It is proved that the method of the present invention can effectively improve the performance of the resistor, and can reduce the amount of additives while still ensuring excellent electrical performance.
[0164] 2. Microstructure comparison
[0165] The samples obtained in Examples 1-2 and Comparative Example 1 were characterized by SEM to study their microstructural differences. Figure 2 As shown, it is a microscopic grain structure characterization diagram at 1k magnification, where: Figure 2 (a) is the SEM image of the sample of Example 1, Figure 2 (b) is the SEM image of the sample of Example 2, Figure 2 (c) is the SEM image of the sample of comparative example 1. As shown in the figure, the Bi-rich phase and spinel of Examples 1-2 are evenly distributed at the grain boundaries, and the grain size is uniform; while in comparative example 1, a triangular area appears, which contains more Bi-rich phase and spinel, and the grain size is dispersed. The uniform distribution of Bi-rich phase and spinel helps to improve the current carrying capacity of the resistor, and the uniform grain size ensures the consistency of the microscopic electrical properties of the resistor, so that the basic electrical properties of the resistor are highly consistent, and the pressure ratio is optimized (this is consistent with the test results in the previous text). It proves that the method of the present invention can optimize the consistency of the performance of the resistor.
[0166] In summary, from the comparison between Examples 1-2 and Comparative Example 1, it can be seen that the present invention uses composite powder technology to prepare zinc oxide varistors, which can make various additive components evenly distributed in the resistor, so that the microscopic performance consistency of the resistor is high, thereby optimizing the performance of the resistor, and its pressure ratio and current density are stronger than those of the resistor prepared by the conventional preparation method under the same formula. And because the uniform distribution of the various components of the additives is improved, the performance of the resistor is still excellent when the additive ratio is reduced. Therefore, the preparation method of the present invention can reduce the amount of additives added, reduce the production cost of the resistor, improve the performance consistency of the resistor, reduce the pressure ratio of the resistor, and increase the current density of the resistor.
[0167] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a zinc oxide varistor sheet, characterized in that: The following steps are involved: A) mixing Bi salt, Sb salt, Mn salt, Ni salt, Co salt and water to obtain a metal salt mixed solution; B) adding a precipitant and a precipitation aid to the metal salt solution in sequence to obtain a solution to be precipitated; C) allowing the solution to be precipitated to settle and separating the solid from the liquid to obtain a precipitate; Then, washing and drying are performed to obtain composite powder; D) subjecting the composite powder, water, ZnO powder and binder to ultrafine grinding and dispersion treatment to obtain a slurry; E) spray drying the slurry to obtain granules; Then, compression molding is performed to obtain a green body; F) heat-insulating the green body in an open atmosphere to remove binder, then pre-sintering it in a closed atmosphere, and then sintering it in a closed atmosphere to obtain a sintered green body; then, performing surface treatment to obtain a resistor; in, The temperature of the heat preservation debinding is 350-500°C and the time is 2-3h; The pre-sintering temperature is 750-950°C and the time is 2-3h; The sintering temperature is 1050-1150° C. and the sintering time is 2-3 hours.
2. The preparation method according to claim 1, characterized in that: In step A): The Bi salt is at least one of bismuth nitrate, bismuth chloride and bismuth citrate; The Sb salt is at least one of antimony nitrate, antimony chloride and antimony citrate; The Mn salt is at least one of manganese nitrate, manganese chloride and manganese citrate; The Ni salt is at least one of nickel nitrate, nickel chloride and nickel citrate; The Co salt is at least one of cobalt nitrate, cobalt chloride and cobalt citrate.
3. The preparation method according to claim 1, characterized in that: In step A), the amount of each metal salt is as follows, based on the molar percentage of the metal element: The concentration of the metal salt mixed solution is 0.5-1.0 mol / L.
4. The preparation method according to claim 1, characterized in that: In step B), the precipitant and the precipitation aid are matched as follows: The precipitant is Na2CO3, and the precipitation aid is NaHCO3; or The precipitant is NH4OH and the precipitation aid is NH4HCO3.
5. The preparation method according to claim 1, characterized in that: In step B), the molar amount of the precipitant is 103% to 110% of the total molar amount of metal ions in the metal salt solution.
6. The preparation method according to claim 1, characterized in that: In step C), the temperature of the static precipitation is preferably 40-50° C. and the time is 1-2 h.
7. The preparation method according to claim 1, characterized in that: Step D) specifically comprises: mixing the composite powder with water and performing ultrafine grinding and dispersion to obtain composite powder slurry; and then adding ZnO powder, a binder and water and continuing ultrafine grinding and dispersion to obtain slurry.
8. The preparation method according to claim 7, characterized in that: When the composite powder is mixed with water for ultrafine grinding and dispersion, the mass ratio of water to composite powder is (1.5-2):1; the speed of the ultrafine grinding and dispersion is 3000-5000 rpm, and the time is 1-2 hours; When adding ZnO powder, binder and water to continue ultrafine grinding and dispersion, the amount of ZnO powder is 85% to 90% of the total mass of the composite powder and ZnO powder; the mass ratio of water to the composite powder slurry obtained in the previous step is (0.5 to 1): 1; the rotation speed of the continued ultrafine grinding and dispersion is 3000 to 5000 rpm, and the time is 1 to 2 hours.
9. The preparation method according to claim 1, characterized in that: In step E), the moisture content of the granular material is 1.2±0.1%; the pressure of the pressing molding is 5-10 MPa, and the holding time is 8-10 seconds.
10. A zinc oxide varistor sheet prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of zinc oxide resistor disc
CN113149634A
Large-through-flow resistor disc distribution process
CN116092761A